2003
DOI: 10.1038/sj.sc.3101421
|View full text |Cite
|
Sign up to set email alerts
|

Deep vein thrombosis and heterotopic ossification in spinal cord injury: a 3 year experience at the Swiss Paraplegic Centre Nottwil

Abstract: Study design: Retrospective review of patient data. Objectives: (i) To determine the incidence and time of deep vein thrombosis (DVT) under low molecular weight heparin (LMWH) prophylaxis in spinal cord injury (SCI), (ii) to determine the incidence and time of heterotopic ossi®cation (HO) and (iii) to assess a possible aetiologic relationship in the pathogenesis of DVT and HO. Setting: Swiss Paraplegic Centre, Nottwil. Methods: We analyzed the incidence of DVT and HO in 1209 SCI patients (275 ®rst rehabilitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 23 publications
(16 reference statements)
0
18
0
2
Order By: Relevance
“…The included studies reported a PE incidence of 0.5%–6.0% and a DVT incidence of 2.0%–8.0% in the sub-acute phase of SCI. This is lower than the 6%–12% incidence in the acute phase of SCI [324]. However, the incidence of PE in the sub-acute phase of SCI remains significantly higher than that of the normal population (0.06%/year) [2526].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The included studies reported a PE incidence of 0.5%–6.0% and a DVT incidence of 2.0%–8.0% in the sub-acute phase of SCI. This is lower than the 6%–12% incidence in the acute phase of SCI [324]. However, the incidence of PE in the sub-acute phase of SCI remains significantly higher than that of the normal population (0.06%/year) [2526].…”
Section: Discussionmentioning
confidence: 99%
“…However, this can also be mimicked by heterotopic ossification or cellulitis [1]. Blood tests including D-dimer are of limited benefit [23] and compression ultrasound is the current mainstay in the diagnosis for DVT. It is widely available, accurate and non-invasive [4].…”
Section: Introductionmentioning
confidence: 99%
“…Symptomatic HO develops in approximately 10% of patients with TBI [10], [11], [12]. In SCI, the HO frequency varies from 5% to 60% depending on the study and whether the diagnosis is based on clinical symptoms or standard radiography results [13], [14], [15], [16].…”
Section: Introductionmentioning
confidence: 99%
“…Even if not strong, there is evidence that LMWHs significantly reduce the incidence of VTE in SCI patients [78][79][80][81][82][83][84][85][86]. For this reason, they represent, alone or in association with IPC, the recommended prophylactic option in these patients, as reported in various guidelines [5, 87,88].…”
Section: Spinal Cord Injuriesmentioning
confidence: 96%